Acquisition of lipid metabolic capability in hepatocyte-like cells directly induced from mouse fibroblasts - Miura, Shizuka; Suzuki, Atsushi (Frontiers in Cell and Developmental Biology, 2014)
Recently, the numbers of patients with non-alcoholic fatty liver disease (NAFLD) and non-alcoholic steatohepatitis (NASH) have increased worldwide. NAFLD and NASH are known as risk factors for liver cirrhosis and hepatocellular carcinoma. Because many factors can promote the progression of NAFLD and NASH, the treatment of these patients involves various strategies. Thus, it is desired that drugs for patients with NAFLD and NASH should be developed more easily and rapidly using cultures of primary hepatocytes. However, it is difficult to use hepatocytes as a tool for drug screening, because these cells cannot be functionally maintained in culture. Thus, in this study, we sought to examine whether induced hepatocyte-like (iHep) cells, which were directly induced from mouse dermal fibroblasts by infection with a retrovirus expressing Hnf4α and Foxa3, possess the potential for lipid metabolism, similar to hepatocytes. Our data showed that iHep cells were capable of synthesizing lipids from a cis-unsaturated fatty acid, a trans-unsaturated fatty acid, and a saturated fatty acid, accumulating the synthesized lipids in cellular vesicles, and secreting the lipids into the culture medium. Moreover, the lipid synthesis in iHep cells was significantly inhibited in cultures with lipid metabolism improvers. These results demonstrate that iHep cells could be useful not only for screening of drugs for patients with NAFLD and NASH, but also for elucidation of the mechanisms underlying hereditary lipid metabolism disorders, as an alternative to hepatocytes.